Możliwości wykorzystania instrumentarium muzycznego Carla Orffa w edukacji muzycznej - od teorii do praktyki edukacji elementarnej = The Possibilities of Application of the Carl Orff`s Music Instruments in Music Education - from Theory to the Elementary Education Teaching Practice - Majzner, Rafał (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The aim of this study is to show the possibilities of application of the music instruments designed by Carl Orff in the elementary education teaching practice. The author of the article presents the results of the research, while simultaneouslytrying to answer questions regarding the purpose and scope of the use of the Orff`s instruments by teachers of elementary education during conducted by them classes and to learn which of the Orff`s instruments are used most often and in what form.
Keywords: instrumentarium Orffa; koncepcja wychowania muzycznego Carla Orffa; muzyka elementarna; Orff`s instruments; concept of Carl Orff`s music education; elementary music